Corrosion Resistance and Electrochemical Adaptation of Aluminium in Brackish Peat Water Sources Under Seawater Intrusion in the Rural Tropical Peatlands of Borneo - Nazeri, Abdul Rahman; Calvin, Jose Jol; Allene, Albania Linus; Badrul Hisham, Mohamad Jan; Arif, Parabi; Chieng, Kwong Ming; Astisza Syahla Ludmilla, Parabi; Anthonette, James; Nur Syazwa, Shamsol; Sebastian Belun, John; Elyza Farhana, Kushairy; Airul Azhar, Jitai; et al. (Elsevier B.V.)
The intrusion of seawater into Borneo coastal peatlands which is driven by climate-induced sea level rise poses a significant challenge to the corrosion resistance of aluminium in water treatment applications. As such, this study aims to investigate corrosion resistance and electrochemical adaptation of aluminium in brackish peat water sources under climate-driven seawater intrusion in the rural tropical peatlands of Borneo. Correspondingly, this study investigates the electrochemical behaviour of aluminium in brackish peat water with varied seawater percentages that ranged from 0% to 100%. When seawater percentage increases from 0% to 50%, Tafel extrapolation reported a pronounced negative shift in the corrosion potential from -337.542 mV to -921.292 mV along with a sharp increase in corrosion current density from 4.581 µA/cm² to 34.290 µA/cm². The corrosive interplay of high salinity levels, acidic, and organic rich conditions in brackish peat water could promotes severe pitting corrosion on aluminium as well as culminating in extensive surface deterioration and the disintegration of its protective oxide film. Additionally, the formulation of isotherm models demonstrate that Langmuir model (R2 = 0.94) accurately describes corrosion kinetics at seawater percentage below 30%. When the seawater percentage being more than 30%, both Freundlich and El-Awady models (R2 > 0.91) provide a better fit which suggest a transition from monolayer to multilayer corrosion mechanisms. Overall, this study deduces the seawater intrusion into brackish peat water sources could accelerate aluminium corrosion which lead to pronounced shifts in electrochemical behaviour and corrosion kinetics.